"Shall I compare thee": The neural basis of literary awareness, and its benefits to cognition. (December 2015) - O'Sullivan, Noreen; Davis, Philip; Billington, Josie; Gonzalez-Diaz, Victorina; Corcoran, Rhiannon
Abstract: Functional magnetic resonance imaging (fMRI) was used to explore the neural and cognitive basis of literary awareness in 24 participants. The 2 × 2 design explored the capacity to process and derive meanings in complex poetic and prosaic texts that either did or did not require significant reappraisal during reading. Following this, participants rated each piece on its 'poeticness' and the extent to which it prompted a reappraisal of meaning during reading, providing subjective measures of poetic recognition and the need to reappraise meaning. The substantial shared variance between these 2 subjective measures provided a proxy measure of literary awareness, which was found to modulate activity in regions comprising the central executive and saliency networks. We suggest that enhanced literary awareness is related to increased flexibility of internal models of meaning, enhanced interoceptive awareness of change, and an enhanced capacity to reason about events. In addition, we found that the residual variance in the measure of poetic recognition modulated right dorsal caudate activity, which may be related to tolerance of uncertainty. These findings are consistent with evidence that relates reading to improved mental wellbeing.